Investigating students’ mathematical literacy: How students solve PISA-like problems in the Jambi context - Tria Gustiningsi; Feri Tiona Pasaribu; Ranisa Junita; Zaleha Ismail (Jurnal Elemen, 2026)
Mathematical literacy is essential for preparing students to solve real-world problems, yet the cognitive processes underlying context-based problem solving remain insufficiently understood. In the PISA framework, mathematical literacy involves the ability to formulate, employ, and interpret mathematics in meaningful contexts. Previous studies have focused primarily on outcomes rather than the processes involved, particularly within local cultural settings such as Jambi. Given the persistent underperformance of Indonesian students in PISA, examining mathematical literacy in a local context is important. This study aimed to analyze students’ mathematical literacy processes using Jambi-based contextual tasks. A qualitative descriptive design was employed involving 24 seventh-grade students selected through purposive sampling to represent high, moderate, and low ability levels. Data were collected through PISA-like written tests and semi-structured interviews and analyzed based on the processes of formulate, employ, and interpret/evaluate. The results showed that 68.06% of students were able to formulate problems, 52.78% successfully employed appropriate mathematical procedures, and only 34.72% correctly interpreted and evaluated solutions. These findings indicate that students experience the greatest difficulty in connecting mathematical results to real-life situations. The research process-oriented assessment and culturally contextualized tasks strengthen students’ interpretative and evaluative competencies in mathematical literacy.